16th IHIW: International Histocompatibility Working Group in Hematopoietic Cell Transplantation. (28th December 2012) - Petersdorf, E. W.; Malkki, M.; Hsu, K.; Bardy, P.; Cesbron, A.; Dickinson, A.; Dubois, V.; Fleischhauer, K.; Kawase, T.; Madrigal, A.; Morishima, Y.; Shaw, B.; et al.
Summary The International Histocompatibility Working Group is a collaborative international effort to understand the HLA and non‐HLA genetics of the transplantation barrier. The Working Group is comprised of experts in the fields of histocompatibility and immunogenetics, hematopoietic cell transplantation and outcomes research. Data for 25 855 unrelated donor transplants were submitted in support of research studies for the 16th International Histocompatibility Workshop. Active investigation is in progress in seven key areas: the impact of HLA matching, role of race and ethnicity, identification of permissible HLA mismatches, haplotype‐associated determinants, minor histocompatibility antigens, immune response genes and KIR genetics. New hypotheses for the 16th workshop were developed for immunogenetic studies in cord blood and haploidentical‐related donor transplantation.